What do internal capital markets do? Redistribution vs incentives - Axel Gautier; Florian Heider (Fondazione Eni Enrico Mattei (FEEM), 2001)
In this paper we explain the apparent ''diversification discount'' of conglomerates without assuming inefficient-cross subsidisation through internal capital markets. Instead we assume that an internal capital market efficiently redistributes scare resources across a conglomerate's divisions between successive production periods. The need for redistribution arises from the fact that resources may sometimes be produced by divisions which happen to be successful in an earlier production stage but which do not have the best investment opportunities in future production stages.In contrast to the existing literature we consider explicitly the incentive problem between corporate headquarter and divisional managers using a standard Moral-Hazard framework. We show that although a complete incentive contract can be written bilaterally between headquarter and divisional managers, the redistribution of resources across divisions creates additional agency costs in a conglomerate.Moreover, assuming that no complete contract can govern the interim redistribution policy by the headquarter, we show how the agency problem with divisional managers constrains headquarters interim redistribution to be ex ante inefficient.
Keywords: G31; G34; L23; 330; Corporate finance; industrial organisation; Betriebliche Finanzwirtschaft; Investition; Konglomerat; Theorie